Familial hypercholesterolemia-associated variants submitted to ClinVar: a ClinGen FH effort - Rita Chora, Joana (2019)
Familial hypercholesterolemia (FH) is an autosomal dominant disorder of lipid metabolism characterized by elevated levels of LDL-C and increased cardiovascular risk. A vast number of potentially pathogenic variants have been identified in FH patients in LDLR, APOB, and PCSK9 genes. We sought to encourage FH researchers/clinicians worldwide to submit their variant findings to the centralized ClinVar database, with the ultimate goal of achieving accurate and consistent variant classification through data sharing and eventual development of FH-specific variant interpretation guidelines.